Reincarnation in Buddhism : an analysis from Islamic perspective / Sheikha Saidah binte Mohamad Najeeb Jarhom - Mohamad Najeeb Jarhom, Sheikha Saidah (2014)
Belief in the concept of reincarnation is a sign of true faith among the Buddhists. A Buddhist has to follow the Four Noble Truth and the Eightfold Path in order to achieve enlightenment which is nirvana. They believe in the rebirth of the soul from the last breath to the liberation of soul which entwines the journey of life from death to karma, to rebirth and finally achieving nirvana. Worshippers of Islam on the other hand have to follow the six Pillars of Faith, the five Pillars of Islam and ihsan which is to do good things in life. They believe in resurrection on the day of Judgement. On this day, Muslims after death will be awaken in the frontiers of barzakh and be judged and placed appropriately in either paradise or hell as promised in the holy Qur’an. By collecting data using documentary method which applied to library materials, the researcher has found that there are still a number of Muslims who were influenced by the traditional beliefs of animism, Hinduism and Buddhism. This is because the Malays were Hindus and Buddhists long before they became Muslim. Even though at this time the Malays are Muslims, the traditional beliefs are still deeply rooted in them. The Malay Muslims influence is within the indigenous belief in spirits, ghosts and reincarnation. On top of that, their culture and traditional practices have also been influenced by Hinduism and Buddhism such as practices of kenduri arwah. Besides that, there are deviant Muslim sects who believe that the idea of reincarnation exists in Islam for instance Al-Arqam and Abu Bakar Bappu. This research aims to analyze the concept of reincarnation from Islamic perspective. Buddhists and Muslims emphasize on moralities, ethics and righteousness plus both believe in death. The major difference in their faith lies in the concept of the hereafter. Buddhism spreads the belief of rebirth, karma and nirvana. Muslims however believe that death occur only once. They will stay in barzakh until the day of Judgement. In contrary to the concept of karma, Islam offers the concept of forgiveness and the purpose of suffering is only a test from Allah. Differences also arise in attaining goals as well as the concept of paradise and hell whereby Buddhists believe that it is primarily a transitory process of achieving nirvana while for Muslims, they are taught to worship Allah in order to enter paradise eternally. Even though Islam rejects the doctrine of reincarnation, the Malay Muslim society is still influenced by the traditional beliefs and practices whereby some of it is erroneous which can lead to polytheism (shirk), a cardinal sin in Islam. This is caused by lack of understanding on Islam as well as fanaticism and extremism towards ones clan. In conclusion, it is a duty for Muslims to make the Muslims realize that some of the customs and traditions of certain ethnics are against the teaching of Islam. Therefore, it is important to understand Islam so it would not be mix up with traditional beliefs which are contrary to the tenets of Islam.